Implikasi Media Sosial terhadap Nilai Religius Siswa MAN Kotawaringin Barat - Nurul Umam; Hamdanah Hamdanah; Saiful Lutfi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Social media is a medium that provides convenience in communication and even interaction without being limited by space and time. Everyone who uses a smartphone has social media installed for their communication access. This communication is needed for interpersonal or intergroup. This is to support mobile activities. The purpose of this study is to determine the implications of social media on the religious values ​​of students at MAN Kotawaringin Barat. This study uses a descriptive qualitative method with a snowball sampling technique which is a type of research that starts with a small sample then develops into a large one until the researcher digs up data with participant observation techniques, in-depth interviews, and documentation. The object of this study is the implications of MAN Kotawaringin Barat social media on students' religious values ​​and the subjects of this study were 31 class XI IPS 1 students with the criteria of actively visiting MAN Kotawaringin Barat social media. The results of this study indicate that the social media of MAN Kotawaringin Barat is still actively used to upload current information and various school activities, but no influence of religious values from the social media of MAN Kotawaringin Barat was found.